Efektivitas Penggunaan E-Tilang Terhadap Pelanggaran Lalu Lintas Di Polres Majalengka - Ratindra, Bayu Okta (Indonesian Journal of Police Studies, 2020)
This study was at The center of his lack of effectiveness regarding the use of E-Tilang as stipulated in the Law No. 22 of 2009 about traffic and road transport in the region of Polres Majalengka. This can be seen from the data indicating that there are still many violators who choose the Court of trial and deposit fines considering that there is currently an application of E-Tilang. E-Tilang is expected to provide easy service, fast and transparency for violators , However, in its execution is not as expected. Therefore, research aims to know the extent of the public knowledge related to the use of e-tilang and how to apply the use of E-Tilang condition today to know the extent of effective use of e-tilang in public life. The study was conducted with a qualitative approach, using descriptive methods of analysis, as well as data collection techniques with interviews, observations and study documents. The Results of the study found that the use of E-Tilang in the region of Polres Majalengka is currently still not effective. This is Due to a few Obstacles such as the lack of public awareness of Community law, which is thepayment access and lack of socialization related to the implementation of E-tIlang. Efforts to improve the effectiveness of e-Tilang use of traffic violations in the police majalengka iegive a place to the community related to what is e-Tilang and provide facilities BRI link when performing the action. Based on the results of the above studies can be concluded the effectiveness of e-tilang against traffic violations in the police majalengka has not been effective. The implementation of the field still has constraints. In addition, there are several factors that affect its use. Addressing this, the Majalengka police have made efforts to improve the effectiveness of E-t, suchAS The addition of BRI link advice and Sosialisi related e-Tilang mechanism as directed by Kapolres Majalengka.